EFFECTS OF A TYPICAL ANTIPSYCHOTIC AND THROMBOXANE A2 SYNTHASE INHIBITOR DRUG COMBINATION ON ALBUMIN AND TOTAL PROTEIN LEVEL WITH DIFFERENT DOSES IN RATS: Effects of Atypical Antipsychotic and Thromboxane A2 Synthase inhibitor drug Combination on Albumin and Total Protein Level - MUHAMMAD IRFAN BASHIR (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of this study was to investigate the combined as well as individual effects of a typical antipsychotic and thromboxane A2 synthase inhibitor on albumin and total protein level with minimum and maximum dose comparison in rats. Methods: This study consisted of 100 albino rats of 300 to 340 g from both gender, there were 10 groups, each contained 10 rats (n=10). Rats were treated with defined dose of zuclopenthixol (Zuclo) and ozagrel (Ozg) for 21 days (3 weeks). Blood samples were collected at 0, 7th, 14th, and 21st days of study. Albumin and total protein level were examined from blood samples using standard laboratory procedure. Results are extracted by applying statistical analysis on data and comparing percentage variation from 0-day value. Results: A typical antipsychotic-treated group showed gradually significant increase in albumin and total protein level, TXA2 synthase inhibitor-treated group also showed significant gradually increase in albumin and total protein level in combination groups, they showed highly significant increase p<0.001 in both parameter with maximum dose. Conclusion: Combination treatment with zuclopenthixol (Zuclo) and ozagrel (Ozg) can cause large increase on albumin and total protein level with maximum dose as compare to individual drug treatment.